The Potential Utilization of Sunan Bonang’s Tomb as Learning Resources : A Preliminary Findings - Mustajab, Imam (Jurnal Paedagogy, 2022)
This study aims to explore and uncover another side of the potentials of Sunan Bonang’s Tomb in relation to its use for educational purposes. Its main focus is the utilization as a learning resource. Through a qualitative research under a case study approach with descriptive data. The data analysis start from data collection through observation, and interviews with local figure and site functionary, also documentation as support. Then step into data reduction, and subsequently the data presentation, later on draw the conclusion of research results. The Results showed that the Tomb of Sunan Bonang contains various potentials that can be utilize in relation to be as a learning resources. From the geographically and architecturally, The Sunan Bonang’s tomb possess opportunities as a learning resource such in Islamic education, history education, moreover multicultural and character education. Its use in the learning process can be through direct or indirect.